2013
DOI: 10.4321/s1130-01082013000300003
|View full text |Cite
|
Sign up to set email alerts
|

Inadequate prescription of chronic consumption of proton pump inhibitors in a hospital in Mexico: Cross-sectional study

Abstract: the frequency of inappropriate prescriptions of chronic use of PPIs was high, around 35.3 %, similar to those reported in hospitals in developed countries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 34 publications
(27 reference statements)
1
12
0
2
Order By: Relevance
“…By comparing patients according to their site of care, the inappropriateness of PPIs prescription was much higher in non-ICU patient compared to ICU patients (87.4 % versus 52.4 %, respectively). Several previous studies reached a similar conclusion and have shown that there was an overuse of PPIs in different clinical settings [10,15,[20][21][22]. Two studies conducted in a major teaching hospital in Tasmania and United kingdom, showed that inappropriate prescription of PPIs were around 60.4 % and 56.0 %, respectively [10,20].…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…By comparing patients according to their site of care, the inappropriateness of PPIs prescription was much higher in non-ICU patient compared to ICU patients (87.4 % versus 52.4 %, respectively). Several previous studies reached a similar conclusion and have shown that there was an overuse of PPIs in different clinical settings [10,15,[20][21][22]. Two studies conducted in a major teaching hospital in Tasmania and United kingdom, showed that inappropriate prescription of PPIs were around 60.4 % and 56.0 %, respectively [10,20].…”
Section: Discussionsupporting
confidence: 53%
“…More recently, it was demonstrated that 61 % of patients admitted to four different hospitals in the state of Maryland received PPIs improperly [15]. In Mexico, the prescription of PPIs was inappropriate in just 35.5 % of the cases [21].…”
Section: Discussionmentioning
confidence: 99%
“…PPIs is a relatively safe type of acid suppression preparations, but overuse can also cause electrolyte metabolism disorders such as calcium and magnesium [7], and increase the risk of infection and other adverse consequences [8], which should be paid enough attention. Indications for the use of drugs for digestive tract gastric acid-related diseases are not accurate enough, which may lead to therapeutic abuse of PPIs [9]. Fear of gastrointestinal bleeding, lack of attention to side effects of acid suppression, and unfamiliar indications for emergency ulcer prevention are the main causes of preventive abuse of PPIs [10].…”
Section: Discussionmentioning
confidence: 99%
“…The overuse of PPIs has been demonstrated in several studies (10)(11)(12). In a study conducted at the Hospital de Guadalajara, Martín-Echevarría et al found that among patients taking PPIs at admission, 73% had an inadequate indication and 38% of patients were discharged with this medication even without correct indication (13).…”
Section: Overuse and Its Consequencesmentioning
confidence: 99%